2021
DOI: 10.3389/fpsyg.2021.643823
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Connections: A Trauma-Informed and Attachment-Based Program to Promote Sensitive Parenting of Trans and Gender Non-conforming Youth

Abstract: Gender non-conforming and trans youth experience high rates of bullying and victimization, placing them at risk for serious mental health challenges. Parent support is one of the most significant protective factors in this population, and yet few programs are specifically developed to promote parenting sensitivity, understanding, and acceptance. Connect, a trauma-informed and attachment-based group program for caregivers of at-risk adolescents, has been shown to reduce parent stress and depressed mood, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
19
0
6
Order By: Relevance
“…The articles were published in 2009 (4.7%) [20], 2011 (4.7%) [21], 2013 (4.7%) [22], 2014 (4.7%) [23], 2015 (4.7%) [24], 2016 (9.5%) [25,26], 2018 (4.7%) [27], 2019 (9.5%) [28,29], 2020 (19%) [30][31][32][33], and 2021 (33%) [34][35][36][37][38][39][40]. All articles (100%) were published in English, of which 14 (66.6%) [20,21,[23][24][25][26][27][28][30][31][32]35,37,40] were from America, 6 (28.5%) [29,33,34,36,38,39] were from Europe, and one (4.7%) [22] was from Oceania. The information and the synthesis of the main results of the final sample of all articles included in the review are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The articles were published in 2009 (4.7%) [20], 2011 (4.7%) [21], 2013 (4.7%) [22], 2014 (4.7%) [23], 2015 (4.7%) [24], 2016 (9.5%) [25,26], 2018 (4.7%) [27], 2019 (9.5%) [28,29], 2020 (19%) [30][31][32][33], and 2021 (33%) [34][35][36][37][38][39][40]. All articles (100%) were published in English, of which 14 (66.6%) [20,21,[23][24][25][26][27][28][30][31][32]35,37,40] were from America, 6 (28.5%) [29,33,34,36,38,39] were from Europe, and one (4.7%) [22] was from Oceania. The information and the synthesis of the main results of the final sample of all articles included in the review are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing gender identity and social transition of transgender children and adolescents is surrounded by guilt, fears, and uncertainties of mothers, fathers, or guardians, who sometimes experience grief related to the ambiguous loss, psychological loss with the person still physically present [7], and of their idealized children [23,24,26,27,30,33,35]. A study carried out in the United States of America (USA) revealed that most parents recognized their children's gender identity, some ignored it, and others were not involved in decisions related to social transition [20].…”
Section: Recognition Of Gender Identity and The Challenges Facedmentioning
confidence: 99%
See 3 more Smart Citations